Perspectivas de la economía alternativa a la hoja de coca - Díaz Gómez, Jorge (2000)
This essay presents the prospects of the alternative crops to the coca leaf, promoted by the Programa de Desarrollo Alternativo (PDA), that has been carried out since 1996 in the coca-growing valleys, and that currently faces a difftcult situation. Although during the 1995-99 period an important increase in the prices and production of coffee and cacao was observed, this situation has reverted ever since, and a large increase of the price of the coca leaf, as well as a significant decrease of the prices of coffee and cacao, have been observed. As a consequence, the small producers of the  coca-growing valleys are abandoning so-called legal crops, among them coffee and cacao, and strongly retaking the production of the coca leaf. In the current situation, characterized by the lack of funding to develop alternative crops to the coca leaf, the possibility that growers agree to finance alternative crops with the profits obtained from the production of the coca leaf should be considered, and, on the other hand, the government and the international cooperation would agree to provide training, technical assistance, as well as to build up communications and other infrastructure.